Developing the Design for a Slotted Agricultural Sprayer and Studying Its Output Parameters - V. E. Slavkina; A. S. Sviridov; G. Arumugam; Y. A. Goncharova; R. M. Kasimov (Сельскохозяйственные машины и технологии)
It is shown that the use of low-quality sprayers for pesticide application can lead to the yield decrease and negative environmental consequences. The use of worn nozzles is noted to reduce the efficiency of plant treatment, since the deviation from the dosage norm of plant protection products reaches 30-60 percent. It is noted that foreign-made sprayers are most often used in Russia, since there are no domestic analogues providing similar output parameters. (Research purpose) To investigate the output parameters of the developed slotted agricultural sprayer and compare them with the performance of advanced imported analogues. (Materials and methods) A prototype model of the developed sprayer was made of bronze using mechanical treatment. It was examined on a special test bench in comparison with a reference polymer sprayer. Using optical microscopy the flow rate of the working fluid and the spray angle were measured, as well as the dimensions of the sprayer nozzle. (Results and discussion) It was found that, on average, in the prototype sprayer made of bronze, the flow rate of the working fluid is 1.7 times greater and the spray angle is 37.16 degrees less than those of a reference polymer sprayer. The examination of the spray nozzles by an optical microscope revealed some differences in shape and size. (Conclusions) The developed design of the sprayer reveals a need for improvement: the nozzle shape should be modified to ellipsoid; the nozzle size should be reduced.